Community Empowerment by Socializing Disaster Management to Increase Knowledge Related to the Mount Raung Disaster in Jambewangi Village, Banyuwangi - Fahmi, Akhmad Yanuar; Belqis, Melania (Al-Hijrah Indonesia, 2024)
One of the natural disasters that often occurs in Indonesia is volcanic eruptions. Volcano disaster management in Indonesia is considered less than optimal because several areas are close to volcanoes and need to implement disaster management properly. Indonesia, with around 13,000 active volcanoes, has caused considerable losses. Mount Raung is an active volcano located in Panjen Hamlet, Jambewangi Village, Sempu District, East Java, with a peak reaching 3,332 meters above sea level and administratively included in three districts, namely Banyuwangi, Bondowoso, and Jember. The respondents used were 20 adolescents aged 18-21 years. The instrument used was a pre-test and post-test questionnaire in a Google Form. The pre-test found that adolescents' knowledge of disaster management needed to be improved. Post-test results found an increase in adolescent knowledge about disaster management to be good. Before respondents received empowerment in Mount Raung disaster management through socialization, they needed more knowledge about Mount Raung disaster management. After the socialization, the data showed that the majority of teenagers in Panjen Hamlet, namely 18 respondents (90%), had a good level of knowledge about Mount Raung disaster management. The implementation of socialization can overcome this problem because socialization is a process of learning, introducing, and disseminating knowledge, ways of life, or social values appropriate to the group to achieve a more developed personality. Socialization is effectively used as an information medium to increase adolescents' knowledge about disaster management.